Characterization of aminoacyl-tRNA synthetase stability and substrate interaction by differential scanning fluorimetry - Abbott, Jamie A. (Methods, 2016)
Differential scanning fluorimetry (DSF) is a fluorescence-based assay to evaluate protein stability by determining protein melting temperatures. Here, we describe the application of DSF to investigate aminoacyl-tRNA synthetase (AARS) stability and interaction with ligands. Employing three bacterial AARS enzymes as model systems, methods are presented here for the use of DSF to measure the apparent temperatures at which AARSs undergo melting transitions, and the effect of AARS substrates and inhibitors. One important observation is that the extent of temperature stability realized by an AARS in response to a particular bound ligand cannot be predicted a priori. The DSF method thus serves as a rapid and highly quantitative approach to measure AARS stability, and the ability of ligands to influence the temperature at which unfolding transitions occur.